2018
DOI: 10.17794/rgn.2018.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Microfacies Characteristics of Carbonate Cobble From Campanian of Slovenj Gradec (Slovenia): Implications for Determining the Fleuryana Adriatica De Castro, Drobne and Gušić Paleoniche and Extending the Biostratigraphic Range in the Tethyan Realm

Abstract: A carbonate cobble was collected in a creek near Slovenj Gradec (Slovenia). It comprises Trochactaeon gastropods as well as foraminifera Fleuryana adriatica and Cuneolina ketini from a subtidal environment with agglutinated and porcelaneous benthic foraminifera. Packstone-grainstone of the structural type contains the abovementioned foraminiferal taxa, which are previously undetermined in this part of the Upper Cretaceous Tethyan realm. Stratigraphic data from this area, together with the determined microfossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Standard thin sections were used for sedimentological analysis and interpretation following the descriptive terminology for carbonate rocks is after Dunham (1962) and Embry and Klovan (1971). The biostratigraphic framework is based on various descriptions of benthic foraminifera (Velić, 2007; including the newest papers like Schlagintweit, 2008;Consorti et al, 2017;Schlagintweit and Rashidi, 2017, Moro et al, 2018, Granero et al, 2019 and planktonic foraminifera (Premoli Silva and Varga, 2004). Because the biostratigraphic range of some the identified species were modified from the time when the geological maps were issued, the discrepancies in age interpretation are indicated in Supplementary Table 1.…”
Section: Methods Of the Laboratory Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard thin sections were used for sedimentological analysis and interpretation following the descriptive terminology for carbonate rocks is after Dunham (1962) and Embry and Klovan (1971). The biostratigraphic framework is based on various descriptions of benthic foraminifera (Velić, 2007; including the newest papers like Schlagintweit, 2008;Consorti et al, 2017;Schlagintweit and Rashidi, 2017, Moro et al, 2018, Granero et al, 2019 and planktonic foraminifera (Premoli Silva and Varga, 2004). Because the biostratigraphic range of some the identified species were modified from the time when the geological maps were issued, the discrepancies in age interpretation are indicated in Supplementary Table 1.…”
Section: Methods Of the Laboratory Investigationsmentioning
confidence: 99%
“…Subsequent studies revealed that Paleocene foraminifera occur below these beds and the K/Pg boundary was allocated to a bed which was interpreted as tsunamite. Therefore, the stratigraphic range of the above-mentioned species was re-defined as being Campanian up to Maastrichtian (Schlagintweit and Rashidi, 2017;Moro et al, 2018). This development induced us to re-visit the Borak/Likva section in 2017 and 2018 for taking GPS co-ordinates and hand samples for biostratigraphic study of the earlier sampled beds (Supplementary Table 1), drill the tsunamites and neighbouring beds.…”
Section: Samplingmentioning
confidence: 99%
“…Microfacies 1 is 10 m in thickness and is developed in the lowest part of the Kazhdumi Formation. Based on the previous study (Moro et al, 2018), this microfacies is assigned to a high‐energy sub‐intertidal environment.…”
Section: Facies Analysismentioning
confidence: 98%
“…Microfacies 1 is 10 m in thickness and is developed in the lowest part of the Kazhdumi Formation. Based on the previous study(Moro et al, 2018), this microfacies is assigned to a high-energy sub-intertidal environment.6.2 | Microfacies 2: Peloid-intraclast-OrbitolinawackestoneThis microfacies is characterized by the presence of agglutinated foraminifers, which are mainly composed of orbitolinids (about 38%).Dasycladacean algae and red algae co-exist with orbitolinids. Nonskeletal grains include intraclasts (20%) and peloids (7%), which are sub-rounded and show medium sorting.…”
mentioning
confidence: 94%
“…In addition, Tethysian benthic foraminifera are also registered in the Angostura Formation, such as Cuneolina ketini Inan, Fleuryana adriática De Castro, Drobne and Gušić, and have also been recorded from Italy and Slovenia by Caffau et al (1998), Tewari et al (2007), and Moro et al (2018); in SW Slovenia (Ogorolec et al, 2007); Turkey (Inan and Inan, 2009;Solak et al, 2017); in Algeria (Tawadros, 2012, p. 448); in Iran, by Schlagintweit and Rashid (2016). In the New World Fleuryana adriatica has been recorded in Guatemala by Fourcade et al, 1999,) (Figure 11).…”
Section: Paleobiogeographymentioning
confidence: 99%